Can a humanoid robot continue to draw attention in an office environment?. (17th July 2020) - Okafuji, Yuki; Baba, Jun; Nakanishi, Junya; Kuramoto, Itaru; Ogawa, Kohei; Yoshikawa, Yuichiro; Ishiguro, Hiroshi
Abstract : This study focuses on the use of humanoid robots in office environments, and investigates whether a robot can maintain the attention of passersby after initiation of face-to-face contact. Drawing attention can be considered as a first step in improving the continuity of use of robots; such continuity is one factor in validating their social acceptance, which must be considered when disseminating robots in offices. In this study, we assume that the robot approaches and greets users in order to make the users aware of its presence and encourage them to use it. In particular, the robots used in this study convey various greetings along with three nonverbal indicators (no motion, random motion, and face-to-face contact) when a passerby at the office is close to the robot. For a one-week period, we validated the social acceptance of the robot by examining how these robot motions influenced the rate and continuity of a passerby's attention. The results revealed that face-to-face contact can draw a high degree of attention, and that the presence of the robot affects the continuity with which attention is drawn. Finally, the paper discusses implications for future robot design, in terms of drawing and maintaining high rates of attention from users. GRAPHICAL ABSTRACT: